Ultrawideband antennas : design and applications - Valderas, Daniel (Imperial College Press, 2011)
Ultrawideband (UWB) technology, positioned as the cutting edge of research and development, paves the way to meet the emerging demands set by broadband wireless applications, such as high-speed data transmission, medical imaging, short-range radars, electromagnetic testing, etc. This breathtaking resource builds upon the basics of UWB technology to provide a complete compilation of figures of merit along with a vital state-of-the-art of the different antenna alternatives that are to be employed according to the specific application. Without excessive recourse to mathematics, this volume emphasizes on the UWB antenna design and equips readers with practical prediction techniques based on simple formulas and models. The big picture of UWB antenna technology would not be complete without addressing its applications, and this will serve to provide consultants with key clues for market gap analysis. Containing over 150 supporting illustrations and figures, this comprehensive overview of UWB technology, antenna design and applications is a vital source of information and reference for R & D organizations, researchers, practitioners, consultants, RF professionals and communication engineers.
Keywords: Ultra-wideband antennas.; Ultra-wideband antennas -- Design.; elektronické knihy; electronic books